Negative electrode and secondary battery

By setting a second layer with a porosity of 5% to 20% in the negative electrode active material layer of the secondary battery, the problem of poor fast charging performance of the secondary battery is solved, and a more efficient charging effect is achieved.

CN119547218APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380050996.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-13
Filing Date
2023-10-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing secondary batteries do not perform well during fast charging, and improper material combinations may affect the final performance of the battery.

Method used

The fast charging performance is improved by providing a double-layer structure in the negative electrode active material layer of the secondary battery, wherein the porosity of the second negative electrode active material layer is 5% to 20% higher than that of the first negative electrode active material layer.

Benefits of technology

Adjusting the porosity difference of the negative electrode active material layer can improve the fast charging performance of the secondary battery, enhance the porosity of the electrolyte close to the negative electrode, and thereby improve charging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547218A_ABST
    Figure CN119547218A_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a secondary battery and a secondary battery comprising the same, the negative electrode for a secondary battery comprising: a current collector; a first negative electrode active material layer provided on the current collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, in which a porosity of the second negative electrode active material layer is 5% to 20% higher than a porosity of the first negative electrode active material layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0131727 filed in the Korean Intellectual Property Office on October 13, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a negative electrode for a secondary battery and a secondary battery including the negative electrode. [Background Technology]

[0003] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EVs) and hybrid electric vehicles (HEVs) driven by an electric driving source.

[0004] Secondary batteries have attracted attention as a new energy source that improves environmental friendliness and energy efficiency due to their major advantages of being able to significantly reduce the use of fossil fuels and using energy without generating byproducts.

[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, etc. In addition, electrodes such as the positive electrode and the negative electrode may be provided with an electrode active material layer on a current collector.

[0006] As the use of secondary batteries increases, a variety of battery performance is required. In order to improve battery performance, attempts are being made to control the composition of active materials or additives in the positive or negative electrode active material layer. However, the wrong combination of materials may have an adverse effect on the performance of the final battery. Therefore, it is necessary to study the use of a combination of positive and negative electrode materials to improve battery performance. [Summary of the invention]

[0007] [Technical issues]

[0008] The present invention has been made in an effort to provide a negative electrode for a secondary battery capable of providing a secondary battery having improved rapid charging characteristics, and a secondary battery including the negative electrode.

[0009] [Technical solution]

[0010] An exemplary embodiment of the present invention provides a negative electrode for a secondary battery, comprising: a collector; a first negative electrode active material layer disposed on the collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the porosity of the second negative electrode active material layer is 5% to 20% higher than the porosity of the first negative electrode active material layer.

[0011] Another exemplary embodiment of the present invention provides a secondary battery including the above-described negative electrode for a secondary battery, a positive electrode, and a separator.

[0012] [Beneficial Effects]

[0013] According to the exemplary embodiment described in this specification, by adjusting the porosity of the two layers in the double-layer structure of the negative electrode active material layer so that they are different from each other, the fast charging performance can be improved. Specifically, the higher the porosity, the more favorable it is for fast charging. When the porosity of the upper layer (the second negative electrode active material layer) is higher than the porosity of the lower layer (the first negative electrode active material layer), although the overall porosity is the same, the porosity of the part close to the electrolyte is higher, resulting in an improved fast charging effect. [Drawings]

[0014] Figure 1 It is a graph showing the chargeable SOC depth of the negative electrodes prepared in Examples and Comparative Examples relative to the C rate. [Specific implementation method]

[0015] Hereinafter, the present invention will be described in more detail to better understand the present invention. The present invention can be implemented in various forms and is not limited to the exemplary embodiments described herein. The terms or words used throughout the specification and claims should not be interpreted as limited to their conventional meanings or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the words or terms in order to best illustrate his invention.

[0016] It will be further understood that when used in this specification, the terms "comprises", "includes" or "has" specify the presence of stated features, numbers, steps, constituent elements and / or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, constituent elements and / or combinations thereof.

[0017] Furthermore, it will be understood that when an element such as a layer is referred to as being "on" another element, it can be "directly on" the other element, or intervening elements may be present. Conversely, when an element is referred to as being "directly on" another element, there are no intervening elements. Furthermore, when an element is referred to as being "on" a reference portion, the element is located above or below the reference portion, which does not necessarily mean that the element is located "above" or "on" in the opposite direction of gravity.

[0018] In this specification, description referring only to “negative electrode active material layer” without the first and second expressions may be applicable to both the first and second negative electrode active material layers.

[0019] A negative electrode for a secondary battery according to an exemplary embodiment of the present specification includes: a collector; a first negative electrode active material layer disposed on the collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the porosity of the second negative electrode active material layer is 5% to 20% higher than the porosity of the first negative electrode active material layer.

[0020] When the porosity of the second negative electrode active material layer is higher than that of the first negative electrode active material layer, although the overall porosity is the same, the porosity of the portion close to the electrolyte is higher, resulting in an improved fast charging effect.

[0021] According to an exemplary embodiment, the porosity of the second negative electrode active material layer may be 5% to 20% higher than the porosity of the first negative electrode active material layer, for example, 10% to 20% higher. In theory, the greater the porosity difference, the better the fast charging performance. However, if the porosity difference is too large, it may have an adverse effect on the life and durability of the battery cell.

[0022] According to an exemplary embodiment, the porosity of the first negative electrode active material layer and the second negative electrode active material layer may be 15% to 40%, respectively.

[0023] According to an exemplary embodiment, the first negative electrode active material layer and the second negative electrode active material layer may contain one or more of a granular conductive material, a linear conductive material, and a planar conductive material as a conductive material. The granular conductive material, the linear conductive material, and / or the planar conductive material contained in the first negative electrode active material layer and the second negative electrode active material layer may be of the same type or of different types.

[0024] Examples of the particulate conductive material may include: graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black.

[0025] Examples of linear conductive materials may include: conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes, for example single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); fluorocarbons; metal powders, such as aluminum and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc.

[0026] Examples of the planar conductive material may include graphene and the like.

[0027] According to one exemplary embodiment, the negative electrode conductive material may be contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of each of the first negative electrode active material layer and the second negative electrode active material layer.

[0028] The first negative electrode active material layer and the second negative electrode active material layer may each contain a negative electrode active material, and the negative electrode active material may include a silicon-based active material and a carbon-based active material. The carbon-based active material may include artificial graphite and / or natural graphite.

[0029] In an exemplary embodiment of the present specification, the silicon-based active material includes SiO x(0 ≤ x < 2), SiM y (where M is a metal and 1 ≤ y ≤ 4) and at least one of Si / C. The silicon-based active material may include only one type, or may include two or more types together. When both negative electrode active material layers include a silicon-based active material, the two active material layers may use the same type of silicon-based active material, or different types or different combinations of silicon-based active materials.

[0030] In one exemplary embodiment of the present specification, based on a total of 100 parts by weight of the negative electrode active material, each of the first negative electrode active material layer and the second negative electrode active material layer may include 1 to 40 parts by weight, for example, 1 to 20 parts by weight of the silicon-based active material.

[0031] The active material containing SiO x (0 ≤ x < 2) may be silicon-based composite particles containing SiO x (0 < x < 2) and pores.

[0032] SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particles. SiO x (0 < x < 2) may be in a form containing Si and SiO2, and Si may form a phase. That is, x corresponds to the ratio of the number of O to Si contained in SiO x (0 < x < 2). When the silicon-based composite particles contain SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0033] The silicon-based composite particles may further include at least one of a Mg compound and a Li compound. The Mg compound and the Li compound may correspond to the matrix in the silicon-based composite particles.

[0034] The Mg compound and / or the Li compound may be present inside SiO x (0 < x < 2) and / or on the surface of SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the Mg compound and / or the Li compound.

[0035] The Mg compound may include at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.

[0036] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Mg element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Mg element may be 0.5% to 8% by weight, or 0.8% to 4% by weight. When the above range is satisfied, the Mg compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during the charge and discharge process of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0037] The Li compound may include at least one selected from the group consisting of lithium silicate, lithium silicide, and lithium oxide. The lithium silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The lithium silicide may include Li7Si2. The lithium oxide may include Li2O.

[0038] In an exemplary embodiment of the present invention, the Li compound may include a lithium silicate form. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the silicon-based composite particles in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5). However, the present invention is not limited thereto.

[0039] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Li element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Li element may be 0.5% to 8% by weight, more specifically 0.5% to 4% by weight. When the above range is satisfied, the Li compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during the charge and discharge process of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0040] The content of Mg element or Li element can be confirmed by ICP analysis. For ICP analysis, after accurately taking a predetermined amount (about 0.01g) of the negative electrode active material, it is transferred to a platinum crucible and completely decomposed on a hot plate by adding nitric acid, hydrofluoric acid and sulfuric acid thereto. Then, by using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer 7300), the reference calibration curve is obtained by measuring the intensity of the standard solution prepared using a standard solution (5mg / kg) at the inherent wavelength of the Mg element or Li element. Subsequently, the pretreated sample solution and the blank sample are introduced into the spectrometer, the actual intensity is calculated by measuring the intensity of each component, the concentration of each component is calculated based on the obtained calibration curve, and then the conversion is performed so that the sum of the calculated concentrations of each component is equal to the theoretical value, and the content of Mg element or Li element in the prepared silicon-based active material can be analyzed.

[0041] In an exemplary embodiment of the present specification, the carbon layer may be disposed on the surface of the silicon-based composite particles and / or inside the pores. The carbon layer imparts conductivity to the silicon-based composite particles, thereby improving the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material containing the silicon-based composite particles. Based on a total of 100% by weight of the silicon-based composite particles, the total amount of the carbon layer included may be 5% to 40% by weight.

[0042] In an exemplary embodiment of the present specification, the carbon layer may include at least one of amorphous carbon or crystalline carbon.

[0043] The average particle size of silicon active materials (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is met, the side reaction between the silicon-based composite particles and the electrolyte can be controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.

[0044] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve of the particles. The average particle size (D) can be measured using, for example, laser diffraction. 50 ). In the laser diffraction method, particle sizes from the submicron range to several millimeters can generally be measured, and results with high reproducibility and high resolution can be obtained.

[0045] The active material including Si / C as the silicon-based active material is a composite of Si and C, and is distinguished from silicon carbide represented by SiC. The silicon-carbon composite may be a composite of silicon, graphite, etc., and may form a structure in which a composite core of silicon, graphite, etc. is surrounded by graphene or amorphous carbon, etc. In the silicon-carbon composite, silicon may be nano-silicon.

[0046] In an exemplary embodiment of the present specification, the content of artificial graphite and natural graphite may be 60 parts by weight or more and 99 parts by weight or less based on 100 parts by weight of the negative electrode active material. The artificial graphite and natural graphite may be included in a weight ratio of 1:9 to 9:1, for example, 2:8 to 8:2.

[0047] In an exemplary embodiment of the present specification, the content of the negative electrode active material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 80 parts by weight or more and 90 parts by weight or less, based on 100 parts by weight of each of the first and second negative electrode active material layers.

[0048] According to one other exemplary embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the negative electrode active material.

[0049] The negative electrode binder can be used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode collector. For the negative electrode binder, those known in the art can be used. Its non-limiting examples may include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and hydrogen are replaced by Li, Na or Ca etc. At least one of the above-mentioned materials in the group consisting of, and their various copolymers may also be included.

[0050] The content of the negative electrode binder may be 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 20 parts by weight, more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0051] In an exemplary embodiment of the present specification, the thickness of each of the first negative electrode active material layer and the second negative electrode active material layer may be 5 μm or more and 100 μm or less, for example, 10 μm or more and 70 μm or less.

[0052] In an exemplary embodiment of the present specification, the negative electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, for the collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium or silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used for the collector. The thickness of the collector can be 1 μm to 500 μm. However, the thickness of the collector is not limited thereto.

[0053] One other exemplary embodiment of the present specification provides a secondary battery including the negative electrode of the above exemplary embodiment, a positive electrode, and a separator.

[0054] In an exemplary embodiment of the present specification, the positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material. The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.

[0055] There is no particular limitation on the positive electrode collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel whose surfaces have been treated with carbon, nickel, titanium or silver, etc., can be used. In addition, the thickness of the positive electrode collector can generally be 1 μm to 500 μm, and the surface of the collector can be formed with fine concave-convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.

[0056] In an exemplary embodiment of the present specification, the positive electrode may include a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material. The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include 80 mol% or more, for example, 80 mol% or more and less than 100 mol% of nickel in a metal other than lithium.

[0057] In an exemplary embodiment, the content of the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0058] According to another exemplary embodiment of the present specification, the positive electrode active material layer of the above exemplary embodiment may further include a positive electrode binder and a conductive material.

[0059] The positive electrode binder can be used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode collector. For the positive electrode binder, those known in the art can be used. Its non-limiting examples can include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, their various copolymers, etc., any one or a mixture of two or more thereof can be used.

[0060] The content of the positive electrode binder may be 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.

[0061] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., any one of which or a mixture of two or more thereof can be used.

[0062] Specifically, in an exemplary embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the composition for the positive electrode active material layer, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, and more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.

[0063] In addition to using the above-mentioned positive and negative active materials, the positive and negative electrodes can be manufactured according to the conventional methods for manufacturing positive and negative electrodes. Specifically, the active material layer-forming composition containing the above-mentioned active materials and optional binders and conductive materials can be applied to the collector, and then dried and rolled to manufacture the electrode. In this case, the types and contents of the positive and negative active materials, binders and conductive materials are as described above. The solvent can be a commonly used solvent in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one or a mixture of two or more thereof can be used. If the solvent can dissolve or disperse the active material, conductive material and binder in consideration of the coating thickness and manufacturing yield of the slurry, and then achieve a viscosity that can show excellent thickness uniformity when coating to manufacture the positive and negative electrodes, the amount of solvent is sufficient. Alternatively, the positive and negative electrodes can be manufactured by casting the active material layer-forming composition on another support, peeling off the film obtained from the support and stacking it on the collector.

[0064] Another exemplary embodiment of the present specification provides a method for manufacturing a positive electrode for a secondary battery of the exemplary embodiment described above. The manufacturing method includes: coating a first composition comprising a negative electrode active material and a conductive material on a current collector and rolling to form a first negative electrode active material layer; and coating a second composition comprising a negative electrode active material and a conductive material on the first negative electrode active material layer and rolling to form a second negative electrode active material layer, so that the porosity of the second negative electrode active material layer is 5% to 20% higher than the porosity of the first negative electrode active material layer.

[0065] The types of specific active materials and conductive materials of each negative electrode active material layer and the manufacturing method of performing separate rolling when forming each negative electrode active material layer can make the porosity of the first negative electrode active material layer different from the porosity of the second negative electrode active material layer, specifically, higher than the porosity of the second negative electrode active material layer. For example, after coating the first negative electrode active material layer, rolling customized for the target porosity can be performed, and after coating the second negative electrode active material layer, rolling customized for the target porosity can be performed a second time, and then they can be dried together.

[0066] The separator is used to separate the negative electrode from the positive electrode and provide a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in secondary batteries, in particular, it is preferred to use a separator having high moisture retention capacity for the electrolyte and low resistance to the migration of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof can be used. In addition, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0067] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in the manufacture of a lithium secondary battery, but are not limited thereto.

[0068] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0069] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.

[0070] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, because they have high dielectric constant, can dissociate lithium salts well, therefore can preferably use.When cyclic carbonate is mixed with the straight-chain carbonate (for example dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant with appropriate ratio, can prepare the electrolyte with high conductivity, therefore can more preferably use.

[0071] Lithium salts can be used as the metal salts. Lithium salts are materials that are easily soluble in non-aqueous electrolytes. For example, lithium salts selected from F - , Cl - ,I -、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、PF6-、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the group consisting of is used as anion of the lithium salt.

[0072] In addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds (such as difluoroethylene carbonate, etc.), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery.

[0073] A secondary battery according to an exemplary embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.

[0074] Another exemplary embodiment of the present invention provides a battery module including the above-mentioned secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capability and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large-sized equipment selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0075] Since the secondary battery of the exemplary embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the secondary battery can be used as a power source for the following devices: portable devices such as mobile phones, notebook computers and digital cameras, and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for any one or more of the following medium and large devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0076] Example

[0077] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes are naturally within the scope of the appended claims herein.

[0078] Example 1

[0079] The first negative electrode active material layer was coated on the negative electrode current collector to a thickness of about 50 μm, and then rolled at room temperature. Next, the second negative electrode active material layer was coated to a thickness of about 50 μm, and then rolled at room temperature. After rolling, they were dried together. Each layer was rolled to achieve the porosity shown in Table 1 below.

[0080] As a composition for preparing the first and second negative electrode active material layers, a composition comprising a negative electrode active material containing artificial graphite, natural graphite and SiO in a weight ratio of 94:1:2:1, a conductive material (containing a linear conductive material (CNT) and a planar conductive material (graphene)), a binder (SBR) and a thickener was used.

[0081] The porosity of each negative electrode active material layer is shown in the following Table 1. The porosity was measured by cross-sectional image analysis and ratio calculation.

[0082] By including Li in a weight ratio of 97:1:2, 1.0 Ni 0.86 Co 0.08 Mn 0.06 The positive electrode is prepared by coating the positive electrode collector with a composition of O2, conductive material (CNT) and binder (PVDF), followed by drying and calendering.

[0083] The battery was prepared by stacking the positive electrode and the negative electrode with a separator and injecting an electrolyte. The electrolyte contained 1M LiPF6, EC (ethylene carbonate) / EMC (ethyl methyl carbonate) (volume ratio 3 / 7), 1.5 wt% Vc (vinyl carbonate) and 0.5 wt% PS (propane sultone).

[0084] Comparative Example 1

[0085] The same procedure as in Example 1 was performed except that the first negative electrode active material layer and the second negative electrode active material layer were coated simultaneously to a total thickness of about 100 μm, and then rolled and dried together.

[0086] [Table 1]

[0087] Porosity of the first negative electrode active material layer (%) Porosity of the second negative electrode active material layer (%) Example 1 18.3 31.7 Comparative Example 1 23.4 26.4

[0088] Figure 1 The chargeable SOC depth of the negative electrode of the battery prepared in the embodiment and the comparative example relative to the C rate is shown. Figure 1 It can be confirmed that the battery prepared in Example 1 shows a greater depth of charge than that of Comparative Example 1.

Claims

1. A negative electrode for a secondary battery, comprising: Current collector; a first negative electrode active material layer disposed on the current collector; as well as a second negative electrode active material layer disposed on the first negative electrode active material layer; The porosity of the second negative electrode active material layer is 5% to 20% higher than the porosity of the first negative electrode active material layer.

2. The negative electrode for a secondary battery according to claim 1, wherein The porosity of the second negative electrode active material layer is 10% to 20% higher than the porosity of the first negative electrode active material layer.

3. The negative electrode for a secondary battery according to claim 1, wherein The porosities of the first negative electrode active material layer and the second negative electrode active material layer are respectively 15% to 40%.

4. The negative electrode for a secondary battery according to claim 1, wherein The first negative electrode active material layer and the second negative electrode active material layer each contain a negative electrode active material, wherein the negative electrode active material comprises a silicon-based active material, artificial graphite and natural graphite, wherein the silicon-based active material comprises SiO x (0≤x<2),SiM y (M is a metal, 1≤y≤4) and at least one of Si / C.

5. The negative electrode for a secondary battery according to claim 4, wherein The silicon-based active material may be contained in an amount of 1 to 40 parts by weight based on 100 parts by weight of active materials contained in total in each of the first negative electrode active material layer and the second negative electrode active material layer.

6. The negative electrode for a secondary battery according to claim 1, wherein The first negative electrode active material layer and the second negative electrode active material layer each contain a conductive material including at least one of a granular conductive material, a linear conductive material, and a planar conductive material.

7. The negative electrode for a secondary battery according to claim 6, wherein: The conductive material may be contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of each of the first negative electrode active material layer and the second negative electrode active material layer. 8 . A secondary battery comprising the negative electrode according to claim 1 , a positive electrode, and a separator.

9. The secondary battery according to claim 8, wherein: The positive electrode includes a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material.

10. The secondary battery according to claim 9, wherein The lithium composite transition metal compound further includes at least one of manganese and aluminum.

11. The method for producing a negative electrode for a secondary battery according to any one of claims 1 to 7, the method comprising: coating a first composition comprising a negative electrode active material and a conductive material on a current collector and rolling the composition to form a first negative electrode active material layer; as well as A second composition including a negative active material and a conductive material is coated on the first negative active material layer and rolled to form a second negative active material layer such that the porosity of the second negative active material layer is 5% to 20% higher than that of the first negative active material layer.

Citation Information

Patent Citations

  • Touch sensing devices and electroniapparatus

    KR1020220131727A